Quality evaluation of shrimp by-product complete ration pellets - Saenab, Andi; Laconi, Erika B.; Retnani, Yuli; Mas’ud, M. Sayuti (Indonesian Animal Sciences Society, 2010)
This research was done to evaluate the physical characteristic and chemical quality of the complete ration in pellet form that contain shrimp by-product.Â The evaluation was done on several variables namely: moisture content, water activity, particle size, average collision endurance, friction endurance and angle of repose. Data obtained was analyzed based on Completely randomized design. The treatment was: R0 (complete ration without shrimps by-product), R1 (complete ration with 10% shrimps by-product), R2 (complete ration with 20% shrimps by-product) and R3 (complete ration with 30% shrimps by-product). The results showed that physical characteristic of the complete ration pellet that contain 20% shrimps by-product had the lowest moisture (13.07%) and the water activity (0.45). Based on the research, it is concluded that the best level of shrimp by-product in the complete ration was 20%. Key words:Â By-Product, Pellet, Digestibility, Sheep